EXPLORING THE REVOLUTIONARY TECHNOLOGY OF INTRAORAL SCANNERS: THE FUTURE OF DENTAL IMPRESSIONS - Sumit Aggarwal (MDS), Sumit Aggarwal (MDS), Deepti Singla (MDS), Roma Goswami (MDS) (Chelonian Research Foundation, 2023)
Impression technologies using CAD/CAM (computer-aided designing and manufacturing) and IOS (intraoral scanner) have been developed for dental practice to address challenges with traditional methods. The choice of technology influences clinical application since there have been more optical IOS devices developed during the past ten years. This article initially provides an overview of the currently employed technologies to enable educated decision-making before acquiring or renewing an IOS. The advantages, and disadvantages, are covered in the second part. The last part pays attention to the accuracy of IOS. Although there are variances in the technologies used, the analysis suggests that the current IOS has been tuned for widespread use. The decrease in hardware volume that has increased the significance of software-based technologies is a significant factor that has been highlighted in this research. Key words- intraoral, scanner, digital, impression.